Virulence Factors and Phylogeny of Staphylococcus aureus Associated With Bovine Mastitis in Russia Based on Genome Sequences - Fursova, Ksenia; Sorokin, Anatoly; Sokolov, Sergey; Dzhelyadin, Timur; Shulcheva, Irina; Shchannikova, Margarita; Nikanova, Daria; Artem'eva, Olga; Zinovieva, Natalia; Brovko, Fedor (Frontiers in Veterinary Science, 2020)
Staphylococcus aureus is a causative agent of different infectious processes, food poisoning and autoimmune disorders. The horizontal transfer of pathogenic strains can occur from animal to human under both house and farm conditions, and the spread of strains with antibiotic resistance is an existing problem. In addition to the spread of antibiotic-resistant strains in clinics, this problem also exists in veterinary medicine. It is especially important to monitor antibiotic resistance on farms where antibiotics are the standard treatment of animals, which may trigger the spread of antibiotic-resistant strains among animals and to the human population, and these strains can also be distributed in milk products produced by these farms (milk, cheese, and butter). In this work, we investigated twenty-one S. aureus isolates using whole-genome sequence analysis and tried to establish a relationship between these isolates with the development of bovine mastitis in seven regions of Western Russia. A S. aureus virulence profile was identified. We identified two groups of S. aureus associated with subclinical mastitis, namely, the enterotoxin-positive and enterotoxin-negative groups. The most prevalent factor associated with bovine mastitis in Russia was cytotoxins, including hemolysins and leukocidins. Multidrug resistance strains were investigated, and antibiotic resistance genes were identified. We identified S. aureus ST 97 type as the most common type in the regions in Western Russia. To the best of our knowledge, this is the first in-depth study of a range S. aureus isolates originating from cattle infections in Russia.